MicroRNA156: a potential graft-transmissible microrna that modulates plant architecture and tuberization in solanum tuberosum ssp andigena - Bhogale, Sneha; Mahajan, Ameya S.; Natarajan, Bhavani; Rajabhoj, Mohit; Thulasiram, Hirekodathakallu V.; Banerjee, Anjan K. (Plant Physiology, 2014)
MicroRNA156 (miR156) functions in maintaining the juvenile phase in plants. However, the mobility of this microRNA has not been demonstrated. So far, only three microRNAs, miR399, miR395, and miR172, have been shown to be mobile. We demonstrate here that miR156 is a potential graft-transmissible signal that affects plant architecture and tuberization in potato (Solanum tuberosum). Under tuber-noninductive (long-day) conditions, miR156 shows higher abundance in leaves and stems, whereas an increase in abundance of miR156 has been observed in stolons under tuber-inductive (short-day) conditions, indicative of a photoperiodic control. Detection of miR156 in phloem cells of wild-type plants and mobility assays in heterografts suggest that miR156 is a graft-transmissible signal. This movement was correlated with changes in leaf morphology and longer trichomes in leaves. Overexpression of miR156 in potato caused a drastic phenotype resulting in altered plant architecture and reduced tuber yield. miR156 overexpression plants also exhibited altered levels of cytokinin and strigolactone along with increased levels of LONELY GUY1 and StCyclin D3.1 transcripts as compared with wild-type plants. RNA ligase-mediated rapid amplification of complementary DNA ends analysis validated SQUAMOSA PROMOTER BINDING-LIKE3 (StSPL3), StSPL6, StSPL9, StSPL13, and StLIGULELESS1 as targets of miR156. Gel-shift assays indicate the regulation of miR172 by miR156 through StSPL9. miR156-resistant SPL9 overexpression lines exhibited increased miR172 levels under a short-day photoperiod, supporting miR172 regulation via the miR156-SPL9 module. Overall, our results strongly suggest that miR156 is a phloem-mobile signal regulating potato development.

MiRNA160 is associated with local defense and systemic acquired resistance against Phytophthora infestans infection in potato - Natarajan, Bhavani; Kalsi, Harpreet S.; Godbole, Prajakta; Malankar, Nilam; Thiagarayaselvam, Aarthy; Siddappa, Sundaresha; Thulasiram, Hirekodathakallu V.; Chakrabarti, Swarup K.; Banerjee, Anjan K. (Journal of Experimental Botany, 2018)
To combat pathogen infection, plants employ local defenses in infected sites and elicit systemic acquired resistance (SAR) in distant tissues. MicroRNAs have been shown to play a significant role in local defense, but their association with SAR is unknown. In addition, no such studies of the interaction between potato and Phytophthora infestans have been reported. We investigated the role of miR160 in local and SAR responses to P. infestans infection in potato. Expression analysis revealed induced levels of miR160 in both local and systemic leaves of infected wild-type plants. miR160 overexpression and knockdown plants exhibited increased susceptibility to infection, suggesting that miR160 levels equivalent to those of wild-type plants may be necessary for mounting local defense responses. Additionally, miR160 knockdown lines failed to elicit SAR, and grafting assays indicated that miR160 is required in both local and systemic leaves to trigger SAR. Consistently, SAR-associated signals and genes were dysregulated in miR160 knockdown lines. Furthermore, analysis of the expression of defense and auxin pathway genes and direct regulation of StGH3.6, a mediator of salicylic acid-auxin cross-talk, by the miR160 target StARF10 revealed the involvement of miR160 in antagonistic cross-talk between salicylic acid-mediated defense and auxin-mediated growth pathways. Overall, our study demonstrates that miR160 plays a crucial role in local defense and SAR responses during the interaction between potato and P. infestans.
Keywords: Auxin-salicylic acid antagonism; microRNA; miR160; Phytophthora infestans; Solanum chacoense; Solanum tuberosum; systemic acquired resistance